Obvladovanje delovne zastarelosti strojev in opreme: količnik ozdravljivosti delovne zastarelosti kot osnova za odločitve o obnovi ali zamenjavi strojev in opreme - Pšunder, Igor (Strojniški vestnik, 2006)
The functional obsolescence of machinery and equipment often appears in the wake of physical deterioration and economic obsolescence. Decisions made about the renovation or replacement of machinery and equipment are mainly based on the last two types of deterioration and are therefore dependent on the physical condition of the machinery and equipment or on external circumstances, e.g., regulation changes. Such decisions are usually not supported by studies of economic feasibility. Economically feasible renovation or replacement of machinery and equipment is usually primarily dependent on functional obsolescence. The paper is a detailed study of the role of functional obsolescence in the process of making decisions about renovation and the replacement of machinery and equipment. We have given special attention to measuring the curability of this obsolescence. We have, for this reason, introduced the term quotient of curability of functional obsolescence. This quotient is based on the relation between the present value of the quantified effects of functional obsolescence for machinery and equipment, and the investment necessary for its repair.
Keywords: stroji; delovna zastarelost; oprema; obnova; zamenjava; cenitev